2012
DOI: 10.21273/horttech.22.4.534
|View full text |Cite
|
Sign up to set email alerts
|

‘Trinidad Moruga Scorpion’ Pepper is the World’s Hottest Measured Chile Pepper at More Than Two Million Scoville Heat Units

Abstract: This study established the heat levels for several high-heat chile pepper (Capsicum chinense) varieties (Trinidad Moruga Scorpion, Bhut Jolokia, Trinidad Scorpion, Douglah Trinidad Chocolate, and Trinidad 7-pot Jonah) to determine which variety has the highest average measured heat level and the relatedness of the chile peppers using molecular analysis. In replicated trials with appropriate controls at Las Cruces, NM, results show two ‘Trinidad Moruga Scorpion’ chile pepper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…Of the 20 accessions with the highest capsaicinoid contents, eight were C. frutescens , seven were C. chinense , and five accessions were C. annuum . The three most pungent accessions, ‘Habanero’, ‘9007’ and ‘Spain 5’, were all accessions of C. chinense , which is well known for its pungency (Bosland and Baral, ; Bosland et al ., ; Canto‐Flick et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 20 accessions with the highest capsaicinoid contents, eight were C. frutescens , seven were C. chinense , and five accessions were C. annuum . The three most pungent accessions, ‘Habanero’, ‘9007’ and ‘Spain 5’, were all accessions of C. chinense , which is well known for its pungency (Bosland and Baral, ; Bosland et al ., ; Canto‐Flick et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…The three most pungent accessions, 'Habanero', '9007' and 'Spain 5', were all accessions of C. chinense, which is well known for its pungency (Bosland and Baral, 2007;Bosland et al, 2012;Canto-Flick et al, 2008). We analysed the association of SNPs with the capsaicin, dihydrocapsaicin and total capsaicinoid contents using GWAS.…”
Section: Gwas For Capsaicinoid Contentmentioning
confidence: 99%
“…It is likely that through anthropogenic influences and long separation from the South American mainland, new varieties have arisen displaying useful plant adaptations and desirable fruit traits. Recent molecular studies revealed the importance of the Caribbean as an important region of this species' diversification (Moses and Umaharan, 2012) as well as a region containing some of the most aromatic pungent peppers in the world (Bosland et al, 2012;Gibbs and O'Garro, 2004;Holder, 2008). As a known region of diversity for C. chinense, the Caribbean varieties could be potentially useful sources of variation in agronomically important traits, e.g., early flowering and fruiting, desired fruit quality traits, suitable plant growth habit, and disease resistance, among others.…”
mentioning
confidence: 99%
“…pericarp [7]. Previous studies have reported that more than 23 types of capsaicinoids were found in peppers [8,9]. Both capsaicin and dihydrocapsaicin were the most abundant capsaicinoids, representing 91% of the total capsacinoids content [10].…”
mentioning
confidence: 99%